Trading Mechanisms and Stock Returns: An Empirical Investigation: Discussion - O'Hara, Maureen (Journal of Finance, 1987)
Maureen O'Hara, Trading Mechanisms and Stock Returns: An Empirical Investigation: Discussion, The Journal of Finance, Vol. 42, No. 3, Papers and Proceedings of the Forty-Fifth Annual Meeting of the American Finance Association, New Orleans, Louisiana, December 28-30, 1986 (Jul., 1987), pp. 554-555